Basic statistics for business and economics - Lind, Douglas A.; Marchal, William G.;Wathen, Samuel A. (Boston, Massachusetts : McGraw Hill Education, 2011)
"As a student of business or economics, you will need basic knowledge and skills to organize, analyze, and transform data and to present the information. In this text, we will show you basic statistical techniques and methods that will develop your ability to make good personal and business decisions."
What is statistics? -- Describing data: frequency tables, frequency distributions, and graphic presentation -- Describing data : numerical measures -- Describing data : displaying and exploring data -- A survey of probability concepts -- Discrete probability distributions -- Continuous probability distributions -- Sampling methods and the central limit theorem -- Estimation and confidence intervals -- One-sample tests of hypothesis -- Two-sample tests of hypothesis -- Analysis of variance -- Linear regression and correlation -- Multiple regression and correlation analysis -- Chi-square applications
Includes index.
Keywords: SOCIAL SCIENCES -- STATISTICAL METHODS